Literature Review on the Role of Mechanical Engineering in Supporting the Industrial Revolution 5.0 - Krisna, Eric (Pt. Anagata Sembagi Education, 2025)
The Industrial Revolution 5.0 marks a paradigm shift from full automation to symbiotic collaboration between humans and machines, emphasizing a human-centric approach, sustainability, and the integration of intelligent technologies. In this context, the role of mechanical engineering has undergone a significant transformation, from merely designing mechanical systems to becoming a multidisciplinary bridge between digital technology and human needs. This study aims to review the literature related to the contribution of mechanical engineering in supporting intelligent manufacturing systems, human-machine collaboration, and the application of sustainability principles such as circular economy and eco-design. Using a qualitative literature study method, data were obtained from indexed academic sources in the last decade and analyzed using a thematic approach. The results of the study indicate that mechanical engineering must integrate artificial intelligence, the Internet of Things (IoT), and cyber-physical systems to support adaptive and efficient production. In addition, the development of cobots requires expertise in safety-based and ergonomic design. In terms of the environment, mechanical engineers are required to apply the principles of product life cycle engineering and low-emission technologies. This transformation creates cross-field challenges that require new competencies and a systemic approach. Therefore, a comprehensive literature review is a strategic basis for formulating the direction of adaptive and sustainable mechanical engineering development in the Industry 5.0 era